2011
DOI: 10.1038/sc.2011.130
|View full text |Cite
|
Sign up to set email alerts
|

25 years or more after spinal cord injury: clinical conditions of individuals in the florence and stockholm areas

Abstract: Setting: Retrospective analysis and retrospective follow-up. Introduction: Spinal cord injury (SCI) patients have today a nearly normal lifespan. Avoidance of medical complications is key to this end. The aim of the study was to analyse health in individuals surviving 25 years or more after traumatic SCI in Stockholm and Florence, and compare medical complications. Methods: Data from the databases of the Spinal Unit of Florence and from the Spinalis, Stockholm were analysed. Patients included were C2-L 2, Amer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 17 publications
2
19
0
Order By: Relevance
“…In the present study, gender, cause of injury, and level and severity of injury were not associated with the occurrence of pain, which is in line with previous reports [37,38]. The occurrence of neuropathic pain among our participants (66%) is greater compared with previous Swedish studies, where 32%‐40% reported neuropathic pain [39,40]. This finding may be explained by an older age at injury in our sample.…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, gender, cause of injury, and level and severity of injury were not associated with the occurrence of pain, which is in line with previous reports [37,38]. The occurrence of neuropathic pain among our participants (66%) is greater compared with previous Swedish studies, where 32%‐40% reported neuropathic pain [39,40]. This finding may be explained by an older age at injury in our sample.…”
Section: Discussionsupporting
confidence: 89%
“…While large, well-designed, population-based studies such as the Stockholm Spinal Cord Injury Study (9) can provide detailed and reliable information, they are often expensive and difficult to conduct longitudinally. More recent studies from Sweden have reported that pain (10)(11)(12)(13), bladder and bowel problems (10,12), pressure ulcers (10,11) and cardiovascular diseases (14) were common problems in individuals with SCI. However, these studies had a narrow focus either related to a specific medical condition or to a specific phase of life after injury, or to a specific age-group.…”
mentioning
confidence: 99%
“…Werthagen et al [17] found that the most common complications in patients with SCI who survived for more than 25 years were found to be pressure ulcers (62%), neuropathic pain (32%), and respiratory ailments (25%).…”
Section: Discussionmentioning
confidence: 99%